Establishment of Recombinant Trisegmented Mopeia Virus Expressing Two Reporter Genes for Screening of Mammarenavirus Inhibitors - Lisa Oestereich; Stephanie Wurr; Beate Becker-Ziaja; Sabrina Bockholt; Meike Pahlmann; Daniel Cadar; Beate M. Kümmerer; Stephan Günther; Romy Kerber (Viruses, 2022)
Highly pathogenic Arenaviruses, like the Lassa Virus (LASV), pose a serious public health threat in affected countries. Research and development of vaccines and therapeutics are urgently needed but hampered by the necessity to handle these pathogens under biosafety level 4 conditions. These containment restrictions make large-scale screens of antiviral compounds difficult. Therefore, the Mopeia virus (MOPV), closely related to LASV, is often used as an apathogenic surrogate virus. We established for the first time trisegmented MOPVs (r3MOPV) with duplicated S segments, in which one of the viral genes was replaced by the reporter genes ZsGreen (ZsG) or Renilla Luciferase (Rluc), respectively. In vitro characterization of the two trisegmented viruses (r3MOPV ZsG/Rluc and r3MOPV Rluc/ZsG), showed comparable growth behavior to the wild type virus and the expression of the reporter genes correlated well with viral titer. We used the reporter viruses in a proof-of-principle in vitro study to evaluate the antiviral activity of two well characterized drugs. IC50 values obtained by Rluc measurement were similar to those obtained by virus titers. ZsG expression was also suitable to evaluate antiviral effects. The trisegmented MOPVs described here provide a versatile and valuable basis for rapid high throughput screening of broadly reactive antiviral compounds against arenaviruses under BSL-2 conditions.